The glass girl : a novel - Glasgow, Kathleen, 1969- (New York : Delacorte Press, 2024)
When fifteen-year-old Bella's latest blackout lands her in the hospital, she enters rehab to confront her addiction to alcohol.
Ages 14+
Keywords: Teenage girls -- Juvenile fiction; Alcoholism -- Juvenile fiction; Rehabilitation -- Juvenile fiction; Mental health -- Juvenile fiction; Families -- Juvenile fiction; Arizona -- Juvenile fiction; Young adult fiction; Social problem fiction; Psychological fiction